Numerical Experiments to Study the Variation of Pressure on India Bhabha Atomic Research Centre Plasma Focus - Arwinder, Singh*; Lee, Sing (Agensi Nuklear Malaysia, 2017)
In this paper a study on the relationship between axial speed va, radial shock speed vs, piston speed vp and pinch temperature with the variation of pressure P0 was carried out. The Lee’s 5 phase model code was used in this study by configuring the India Bhabha Atomic Research Center (BARC) plasma focus machine to operate in the pressure (P0) range from 1 Torr to 14 Torr.